PEMBENTUKAN GERAK TARI DILA PANGETO KARYA INDRA JAYA DI KABUPATEN SUMBAWA BARAT NUSA TENGGARA BARAT - A Azizah; Matheus Wasi Bantolo (Greget, 2019)
AbstractDila Pangeto Dance is a work created by Indra Jaya in 2016. This research will emphasize the choreography which includes Indra Jaya as the creator, the idea of creation about the world and education, the process of creation that there is exploration, improvisation, and composition, as well as the formation of dance motion Dila Pangeto. To discuss the above problems using the foundation of Theory: Choreography using Seymour theory, the form of servings using the theory of Suzanne K. Langer, and formation of motion using the theory of Doris Humphrey. This dance research uses a descriptive method of analytic with qualitative data types through the data collection stage i.e. observation, interviews, library studies, as well as data analysis stage. The results of the study were the choreography Dila Pangeto which discusses the creators, ideas of creation, and the process of creation and the form of dance in which there is a serving structure divided into five parts, and the dance elements of Dila Pangeto include two female dancers, a parallel floor pattern, and zigzag, the stage space that has been provided by the organizing committee, dressing and clothing using West Sumbawa costumes, Dila and shawl properties, West Sumbawa Music and the addition of violin instruments, as well as Motion derived from the motion of West Sumbawa Dance and Gentao or Pencak Silat. The formation of Dila Pangeto Dance uses the motion of West Sumbawa Dance and Gentao. The formation of the dance movements of Dila Pangeto in the movement patterns such as Ngengke ‘, Palangan Telas, Nyempung, Bagerik, plump besai ‘, Bolang sweep ‘, Juluk Betak, Pio Ngibar, remove Pengkenang, Betak Jala, Sempanang, Telnyak ninting, Pusuk nyer, puntal yarn, Nesek , ninting Seleng, ente Dila, swivel dila, Jonyong, Basalunte ‘, Tanak, Ngijik, and Bajempit contains more designs using a unidirectional line design, the dynamics of gentle motion, functional rhythm or rhythm, mechanisms, and emotional The motivation of the life of West Sumbawa. Characters and character in each motion pattern the Dila Pangeto dance has a gentle, polite, and graceful character.Keywords: Dila Pangeto dance, Indra Jaya, choreography, and formation Motion.